2013
DOI: 10.1186/1742-2094-10-24
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral ischemia initiates an immediate innate immune response in neonates during cardiac surgery

Abstract: BackgroundA robust inflammatory response occurs in the hours and days following cerebral ischemia. However, little is known about the immediate innate immune response in the first minutes after an ischemic insult in humans. We utilized the use of circulatory arrest during cardiac surgery to assess this.MethodsTwelve neonates diagnosed with an aortic arch obstruction underwent cardiac surgery with cardiopulmonary bypass and approximately 30 minutes of deep hypothermic circulatory arrest (DHCA, representing cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Emerging evidence has demonstrated that hypoxia-ischemia induces the inflammatory responses in the brain parenchyma and the peripheral immune system, which play a critical role in mediating secondary neuronal death (Algra et al , 2013; Wang et al , 2010). In the neonatal brain, an immediate innate immune response occurs within minutes after the HI insult.…”
Section: Neuro-immune Communication In Neonatal Hi Brain Injurymentioning
confidence: 99%
“…Emerging evidence has demonstrated that hypoxia-ischemia induces the inflammatory responses in the brain parenchyma and the peripheral immune system, which play a critical role in mediating secondary neuronal death (Algra et al , 2013; Wang et al , 2010). In the neonatal brain, an immediate innate immune response occurs within minutes after the HI insult.…”
Section: Neuro-immune Communication In Neonatal Hi Brain Injurymentioning
confidence: 99%
“…Within hours after an insult to the brain of an adult, cytokines are produced in large amounts, and leukocytes are activated and migrate into the injured brain 10,11,12,13,14 . In neonates, however, cerebral ischemia initiates an immediate innate immune response even minutes after the insult 15 . Age differences in the mechanisms of stroke, some of them very striking, stem from immaturity of the CNS, including differences in the cross-talk between excitotoxic, oxidative and inflammatory injury mechanisms, creating “windows of susceptibility” to hypoxic-ischemic injury during embryonic and early postnatal brain development 16 .…”
Section: Introductionmentioning
confidence: 99%
“…A robust inflammatory response follows shortly after hypoxia-ischemia (HI) [2] , potentially providing both neuroprotective and damaging effects [3][4][5] . Innate immune responses are activated within minutes after ischemia [6] , resulting in the release of inflammatory cytokines such as interleukin (IL)-1β and IL-18. The NLRP3 inflammasome is the principal activator of IL-1β and IL-18 [7] .…”
Section: Introductionmentioning
confidence: 99%